Divided Eastern Europe : Borders and Population Transfer, 1938-1947. - Dyukov, Aleksandr (Cambridge Scholars Publishing, 2012)
In 1938, on the eve of what would mark the beginning of the Second World War during the international crisis, Eastern Europe was divided - in every sense of the word. New governments, which were generally regarded as national states, rose from the ashes of the old pre-modern Austro-Hungarian and Russian empires. However, civic nations were not formed Otherin them; the titular ethnic groups were far from being the only representing populations in these states. The new states in Eastern Europe w ...